Strategiczny controlling projektów - Kozarkiewicz-Chlebowska, Alina (Strategic controllership projects, 2006)
The main aim of this paper is to discuss the need for distinguishing the concept of strategic controllership of projects as well as to define this concept and describe its scope and instruments. In the second part of this article the major tools of strategic controllership of projects are briefly presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 228-237